What pandemic can teach us about the "right" to die - Albert Márquez, Marta (2020)
The article tries to illustrate how the debate on the right to euthanasia can be rethought in the post-Covid society. It is claimed that the legalization of euthanasia generates a risk to the life and integrity of the people who are granted the right to die, the patients with a severe chronic disease. The pandemic has highlighted the enormous vulnerability of these patients in the exercise of their right to health protection and the need for more effective legal protection for their lives. Similarly, the health crisis allows us to re-dimension the real demands of the hypothetical recipients of the new Euthanasia’s law, and these have less to do with the right to death than with the right to life and equal access to available medical treatment.